TAXABLE SOURCES OF LOCAL BUDGET REVENUES AND THEIR EFFICIENCY - Isakov, Zafarjon Zokirjonovich (THE INNOVATION ECONOMY, 2026)
This article scientifically analyzes the main tax sources of local budget revenues, their economic content, and their role in ensuring the financial stability of regions. It also presents conclusions on issues of increasing the efficiency of tax revenues and improving existing mechanisms.